Staff recruitment using expert system / Mohd Hassan Fahmi Nordin - Nordin, Mohd Hassan Fahmi (2012)
Companies nowadays had to face the challenges of hiring the right talent. The main strategy for recruiting new talent that most organizations rely on now is interview. Staff Recruitment Using Expert System is designed to choose the eligible applicant for the lecturer’s position at UiTM Terengganu. Expert system is one of the artificial intelligent (Al) techniques that can implement in many areas. This research is to develop a protoype of staff recruitment using expert system which inference technique had been choosen is forward chaining technique. The system will identify by using the criteria that has been set up by the admin such qualification, age, citizen, the grade of bahasa Melayu in Sijil Peperiksaan Malaysia (SPM) and compare with the criteria that has been input by the applicant. This research methodology consists of five stages which are preliminary study, knowledge acquisition and comprehension, system and rule design, system development and finally testing. The data was gathered from the Management Department in UiTM Terengganu. The system is a web-based system and developed using PHP as programming language and MySql as database tool. In future, it is recommended that the prototype can learn from experience.